ForkMatic (automated railed forklift) - Mohamad Zambri, Nurul Ain; Azman, Nurshella; Abd Hamid, Hidayah Salwa; Selamat, Muhammad Adi Daniel; Mohd Razali, Muhammad Hadif Azfar; Ariffin, Nurul Azrin (Universiti Teknologi MARA, Negeri Sembilan, 2025)
The development of ForkMatic, an AI-powered rail-mounted autonomous forklift, addresses key challenges in warehouse operations by automating material handling tasks. Unlike traditional manual forklifts, ForkMatic enhances safety and productivity by minimizing human errors and reducing dependency on skilled operators. The system integrates seamlessly with Warehouse Management Systems (WMS) to provide real-time updates on inventory, improving stock tracking and order fulfillment times. With a focus on reducing labor costs, increasing operational efficiency, and ensuring precise material handling, ForkMatic is a scalable solution suitable for various sectors including logistics, retail, and healthcare. Its design prioritizes sustainability through the use of energy-efficient components and recyclable materials, making it an eco-friendly choice for modern warehouses.